Too Many Hats? Conflicts of Interest in Learning Community Faculty Roles. (February 2019) - Gliatto, Peter; Colbert-Getz, Jorie M; Bhutiani, Monica; Cutrer, William B; Edwards, Sharon; Fleming, Amy; Keeley, Meg; Osterberg, Lars; Pilla, Michael A; Moynahan, Kevin
Purpose: Many US medical schools have adopted learning communities to provide a framework for advising and teaching functions. Faculty who participate in learning communities often have additional educator roles. Defining potential conflicts of interest (COIs) among these roles is an important consideration for schools with existing learning communities and those looking to develop them, both for transparency with students and also to comply with regulatory requirements. Methods: A survey was sent to the institutional contact for each of the 42 Learning Communities Institute (LCI) member medical schools to assess faculty opinions about what roles potentially conflict. The survey asked the role of learning community faculty in summative and formative assessment of students and whether schools had existing policies around COIs in medical education. Results: In all, 35 (85%) LCI representatives responded; 30 (86%) respondents agreed or strongly agreed that learning community faculty should be permitted to evaluate their students for formative purposes, while 19 (54%) strongly agreed or agreed that learning community faculty should be permitted to evaluate their students in a way that contributes to a grade; 31 (89%) reported awareness of the accreditation standard ensuring "that medical students can obtain academic counseling from individuals who have no role in making assessment or promotion decisions about them, " but only 10 (29%) had a school policy about COIs in education. There was a wide range of responses about what roles potentially conflict with being a learning community faculty. Conclusion: The potential for COIs between learning community faculty and other educator roles concerns faculty at schools with learning communities, but most schools have not formally addressed these concerns.